Evaluation of Nigerian Undergraduates on Media and Film Literacy - Ramson Oloche Acheme; Steven Anu’ Adesemoye; Perpetua Ogechi Aondover; Charles Adewale Olugbenga; Oche Sunday Odihi (LingLit Journal Scientific Journal for Linguistics and Literature, 2025)
Media, and film in particular, are not only popular medium among contemporary Nigerians, but they have become critical source of concerns for media scholars. Given to the fact that film permeate our world through the multiplex phenomenon and the internet, it has become a major concern to investigate the level of film literacy among young Nigerian viewers. Renowned media scholar Stuart Hall argued that filmmakers embed certain messages in their narratives and the viewers most times, decode the messages, while others form an opposite view of what the filmmaker originally intended. With the pervasiveness of film/movies on the internet and other modern technologies, it is pertinent to examine the level of film literacy of Nigerian youths. Consequently, undergraduates from Nigerian universities in Southwestern part of the country were served a 19-item questionnaire through Google Form. A link was sent to mass communication students in Caleb University, Christopher University, NOUN Ikorodu campus, Lagos State University of Science and Technology, and Wesley University- Lagos annex. 336 responses were recorded and tabulated. Findings reveal that Nigerian undergraduates have some level of media literacy as a reasonable number of the respondents attest that they are ware of filmmakers’ motive in the narratives, and they admitted that film contents influence their life purview. They agreed that film is a good and one of the fastest ways to reach the people with any behaviour change message. This study anchored on the uses and gratification theory-UGT, recommends that further field studies be launched into this topic to clear some grey areas. For instance, a new study should probe how Nigerian undergraduates make sense of the foreign and local movies about their culture.